Dampak Komunikasi, Konflik Kerja, Lingkungan Kerja dan Motivasi Kerja atas Kinerja Karyawan PT. Samawood Utama Works Industries - Sifra Anju Norita; Marcello Lawrence (Journal of Management and Bussines (JOMB), 2023)
This research aims to examine and analyze the impact of communication, work conflict, work environment and work motivation on the performance of PT employees. Samawood Utama Works Industries independently and simultaneously. The research method is quantitative descriptive, with an explanatory nature. 78 employees at PT. Samawood Utama Works Industries is the population in the study. The research results produce communication, work conflict, work environment and work motivation independently and simultaneously influencing the performance of PT employees. Samawood Utama Works Industries. The variation of the independent variable over the dependent variable is 87.3%, the excess of 12.7% is explained by other factors not included in this study, such as Organizational Commitment, Job Stress, Compensation, etc. The conclusion from the results of this research is that communication, work conflict, work environment and work motivation independently or simultaneously have an impact on employee performance. Keywords: Work Conflict,Work Environment, Work Motivation, Employee Performance